17.2 NEGATIVE SYMPTOMS IN THE OPTiMISE COHORT: PREDICTION OF SHORT-TERM REMISSION STATE AND ASSOCIATION WITH PSYCHOSOCIAL FUNCTIONING. (9th April 2019) - Mucci, Armida; Vignapiano, Annarita; Bucci, Paola; Glenthoj, Birte; Arango, Celso; Martinez-Caneja, Covadonga; Rodriguez-Jimenez, Roberto; Winter, Inge; Galderisi, Silvana
Abstract: Background: Negative symptoms represent an unmet need of schizophrenia treatment, occurring since the early phases of the disorder. Primary and persistent negative symptoms are associated with the worst outcome in terms of treatment response and psychosocial functioning. The prevalence of these symptoms in first episode patients, especially early after onset (within 2 years), has not been systematically studied. Methods: In the present study we investigated the prevalence of negative symptoms of moderate severity, unconfounded by depression and extrapyramidal symptoms at baseline (U-NEG), and their persistence over the three phases of the OPTIMISE trial (i.e., after 4, 10 and 22 weeks of treatment). The impact on remission and psychosocial functioning of persistent negative symptoms (PNS) was also assessed. Results: U-NEG were observed in 263/446 subjects (59% of the whole cohort of first-episode, recent-onset subjects). U-NEG were associated with worse psychosocial functioning and duration of psychosis at intake in the study. At the end of phase2 they were associated with poor psychosocial functioning (controlling for the severity of all other psychopathological dimensions and demographic variables). However, the attrition and remission rates did not differ with respect to subjects without negative symptoms of moderate severity. U-NEG persisted in 49 subjects (11% of the whole cohort and 18.6% of cases with U_NEG) at the end of phase1 (after 4 weeks of amisulpride treatment). The 49 early PNS subjects did not differ at baseline on measures of functioning and global severity of illness from non-persistent U-NEG subjects (NPNS), although the latter group had more severe depression and positive symptoms. At the end of phase1, PNS subjects had higher global severity of illness, were less frequently remitted and showed a worse psychosocial functioning than NPNS. During phase2 (6 weeks double-blind olanzapine vs amisulpride), 22/49 PNS subjects dropped (44.9%) vs 45/214 (21%) of NPNS. Among the 27 PNS who completed phase2, 13 (48.1%) were non-remitted and started phase3, representing 72% of all subjects entering phase3 (N=18). Only 10 subjects completed phase3 and 7 were non-remitted. These latter subjects had persistent negative symptoms across all treatment phases. Conclusions: Unconfounded negative symptoms predicted poor psychosocial functioning. Persistent negative symptoms were associated with the worse psychosocial functioning at all phases and were the most resistant to antipsychotic treatment including clozapine.